Positive Solutions for a System of Semipositone Fractional Difference Boundary Value Problems - Cheng Chen; Jiafa Xu; Donal O’Regan; Zhengqing Fu (Journal of Function Spaces)
Using the fixed point index, we establish two existence theorems for positive solutions to a system of semipositone fractional difference boundary value problems. We adopt nonnegative concave functions and nonnegative matrices to characterize the coupling behavior of our nonlinear terms.